Assessment of Common Practical Skills in Clinical Medical Students in Shiraz, Fasa and Jahrom Universities of Medical Sciences: A Cross-sectional Study - Esmail Rayat Dost (Journal of Global Pharma Technology, 2017)
Introduction: This study has been conducted to assess common practical skills in clinical medical students in Shiraz, Fasa & Jahrom Universities of Medical Sciences. The ability for practical skills is an important goal for medical education and these skills are essential for the diagnosis and treatment of diseases. As a result, the present study has been carried out with aim of evaluating common practical skills in clinical medical students in Shiraz, Fasa & Jahrom Universities of Medical Sciences. Method: The present study is a cross-sectional study. In this study, 100 internship students were selected and data were collected by questions about 25 clinical skills. Data analysis was performed by SPSS software version 11 and statistical tests. Results: The results showed that the capabilities of medical students in practical skills are far from the ideal situation. 78% of students believed that they did not have the necessary ability to do practical skills. Most of them have not gained these skills under the supervision of qualified persons. 82 percent of students evaluate the quality of education in these procedures unfavorable. And a high percentage of them believed that they needed to retrain these skills. Conclusion: This study demonstrated that no attention has been paid to practical skills training and therefore teaching students about the clinical skills before entering the clinical departments is very important.Keywords: Medical education, Practical skills, Evaluation of medical students.